A Periareolar Approach for Skin Cancer Adjacent Nipple–Areolar Complex - Tuan-Anh Bui, MD; Hsiang-Shun Shih, MD; Seng-Feng Jeng, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. The periareolar approach has been successfully used in our cosmetic patients, including cases of mastopexy, breast reduction, and severe gynecomastia surgery, demonstrating its efficacy in achieving favorable cosmetic outcomes. However, so far in the English literature, there is no report of using this technique for the reconstruction of skin cancer adjacent to the nipple–areolar complex. A 58-year-old woman presented with basal cell carcinoma on the skin of her right breast, adjacent to the areola. The tumor, measuring 4 × 4 cm, was surgically excised with clear margins. Reconstruction was performed using a periareolar approach, using a purse-string suture technique reinforced with subcutaneous buried sutures to minimize tension instead of using a skin graft or local flap for reconstruction. This method aimed to achieve minimal external scarring by camouflaging the scar at the junction between the chest skin and the nipple–areolar complex.